The influence of natural seasoning on the load capacity of cylindrical adhesive joints - Zielecki, Władysław; Guźla, Ewelina; Bielenda, Przemysław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2021)
The aim of the work was to investigate the influence of natural seasoning on the load capacity of cylindrical adhesive joints subjected to and not subjected to additional heat treatment. The adhesive joints ware made of ENAC-AlSi7Mg0.3 aluminum alloy (sleeve) and glass-epoxy composite (pivot). The elements were joined together using the Araldite 2014 adhesive composition. The adhesive joins were subjected to an axial shear test. The research was carried out for several variants of seasoning: seasoning for 6 months in the summer period, seasoning for 6 months in the winter period, seasoning for one year and two years. The test results show that the seasoning of samples not subjected to additional heat treatment increased the load capacity of the adhesive joints by 0.1-21.3%. On the other hand, in the case of samples subjected to additional heat treatment, seasoning contributed to the reduction of the load capacity of the joints by 0.6-24%. The analysis of significant differences (Student’s t-test) showed that in the adopted range of variability of the input factors, the seasoning conditions did not have a significant impact on the load capacity of the adhesive connections. Only in the case of samples with additional heat treatment, seasoned for 2 years, the load capacity shows statistically significant differences compared to other variants (pv=0.23%). The results of correlation and regression analysis indicate that in the case of samples subjected to additional heat treatment, the load capacity of the adhesive joints decreases with the increasing duration of seasoning (r=-0.835). In the case of samples that have not been subjected to additional heat treatment, the load capacity of the joints increases with the increasing duration of seasoning (r=0.841). This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)